2023
DOI: 10.1111/aogs.14618
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers at 6 weeks' gestation in the prediction of early miscarriage in pregnancy following assisted reproductive technology

Abstract: Introduction Miscarriage is a major concern in early pregnancy among women having conceived with assisted reproductive treatments. This study aimed to examine potential miscarriage‐related biophysical and biochemical markers at 6 weeks' gestation among women with confirmed clinical pregnancy following in vitro fertilization (IVF)/embryo transfer (ET) and evaluate the performance of a model combining maternal factors, biophysical and biochemical markers at 6 weeks' gestation in the prediction of first trimester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
2
0
2
Order By: Relevance
“…Хронічний ендометрит відмічається в понад 40% пацієнток із непліддям [6,7]. У пацієнток із невдалими спробами екстракорпорального запліднення в анамнезі ця патологія є ключовим фактором невдалих повторних імплантацій ембріонів і самовільних переривань вагітності та відмічається у 30-60% випадків [4,5].…”
Section: оригінальні дослідженняunclassified
See 1 more Smart Citation
“…Хронічний ендометрит відмічається в понад 40% пацієнток із непліддям [6,7]. У пацієнток із невдалими спробами екстракорпорального запліднення в анамнезі ця патологія є ключовим фактором невдалих повторних імплантацій ембріонів і самовільних переривань вагітності та відмічається у 30-60% випадків [4,5].…”
Section: оригінальні дослідженняunclassified
“…У пацієнток із невдалими спробами екстракорпорального запліднення в анамнезі ця патологія є ключовим фактором невдалих повторних імплантацій ембріонів і самовільних переривань вагітності та відмічається у 30-60% випадків [4,5]. Вона також верифікується в близько 72% гістологічних зразків біоптатів слизової оболонки матки в жінок із перенесеними в анамнезі інфекціями, що передаються статевим шляхом, та у 12-68% жінок із трубно-перитонеальними формами непліддя [6,17]. Також висока частота цього захворювання (від 33% до 87%) спостерігається в пацієнток зі звичним невиношуванням вагітності [8][9][10].…”
Section: оригінальні дослідженняunclassified
“…The development of CE is associated with a number of pathological processes that significantly affect the functional state of the uterine mucosa, thereby creating unfavorable conditions for the onset of pregnancy [4,5]. These are primarily related to destructive changes in endometrial cells that occur during prolonged infl ammation [6], impaired microcirculation in the basin of the uterine spiral arteries [4], inadequate transformation of the uterine mucosa during the menstrual cycle [4][5][6][7], as well as a decrease in the synthesis of α2-microglobulin of fertility (also known as glycodelin-A) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, a decrease in the level of fer tility α2-microglobulin (glycodelin-A) was demonstrated in women with CE both in the preconception stage and during the first weeks of pregnancy [2,7]. Adequate synthesis levels create favorable conditions for implantation and embryonic development [8,9], as well as ensure adequate progression of trophoblast invasion into the uterine spiral arteries, which is a necessary step in the formation of adequate feto-maternal blood fl ow [10,11]. The processes of trophoblast invasion into the spiral arteries of the uterus are crucial for the entire process of pregnancy, and their disruption leads to the development of serious obstetric pathologies (such as pregnancy loss, pre-eclampsia, intrauterine growth restriction, placental abruption) [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%